Pedagogic practices in a deregulated upper secondary school: Students' attempts to influence their teaching. (November 2019) - Bjarnadóttir, Valgerður S.; Öhrn, Elisabet; Johansson, Monica
This article explores strategies, targets, and responses to young people's attempts to influence pedagogic practices, and the variations between different programmes in a deregulated upper secondary school system. Using Basil Bernstein's code theory, the study draws on ethnographic data from two of the most popular academic programmes in one upper secondary school in Iceland, the natural science programme and the social science programme. Students tried to a greater extent to influence the 'how' of their everyday education rather than the 'what'. That is, neither of the student groups tried to influence the content of their lessons or courses. There was a strong framing of the selection of knowledge but variations in the framing of pacing and teaching methods, which presented students with various options as to what they tried to influence. The findings imply that mathematics within the natural science programme was a gatekeeper to students' further studies as it was strongly framed and classified, and students' attempts to slow down the pacing were unsuccessful. The students in the social science programme targeted monotonous teaching methods, without success. Some of the students responded to the failed attempts by interrupting classes and reducing lesson time for the whole group. The findings indicate that the deregulation of the upper secondary school curriculum needs to be considered, as it leads to stronger classification between schools, subjects, and programmes.